Neutrophil-Lymphocyte Ratio Related to Patients Outcome in Moderate Head Injury Patients with Intracerebral Hemorrhage - Vandra Prinosa; Syaiful Saanin; Ade Ricky Harahap (HM Publisher, 2022)
Background. Head injury is still a major health problem that is a common cause of disability and death. Moderate head injuries are quite common with outcomes varying patient examination of neutrophils and lymphocytes is quite routinely carried out in health services and the combination of these two values has a stronger predictive value for assessing outcomes in patients because it describes an inflammatory reaction. The GOS is a commonly used scale for classifying patient outcomes. This study aimed to determine the relationship between the ratio of neutrophil-lymphocytes (RNL) to the Glascow outcome scale (GOS) in moderate head injury patients with intracerebral hemorrhage. Methods. This study has a cross-sectional with samples from moderate head injury patients with CT scan images of intracerebral hemorrhage in Dr. M. Djamil Padang in 2021 and 2022. The data comes from medical records and observations of samples that meet the inclusion and exclusion criteria, 36 subjects participated in this study. Results. Most of the subjects (61.1%) were male. A total of 55.6% of subjects had RNL ≥ 7.35 with 44.4% of subjects having poor GOS. In this study, a statistically significant relationship was found between the ratio of neutrophil- lymphocytes in patients with moderate head injury with intracerebral hemorrhage and the Glasgow outcome scale (p-value = 0.005). Conclusion. RNL can predict outcomes in moderate head injury patients with intracerebral hemorrhage.